Pendidik Islam Menurut Syekh Burhanuddin Az-Zarnuji dan Implikasinya bagi Profesionalisme Guru - Faizin, Moh.; Rahma, Alia Nafisah; Khildan, Salsabil Nur Shilfiya (Moderasi : Journal of Islamic Studies, 2025)
The role of educators in Islamic education is highly significant, particularly in addressing contemporary educational challenges that tend to prioritise cognitive achievement over character formation. This article examines the concept of the Islamic educator according to Syekh Burhanuddin Az-Zarnuji in Ta'lim al-Muta'allim li Thariq al-Ta'allum and analyses its implications for modern teacher professionalism. This study employs a descriptive–analytical literature review, using Ta'lim al-Muta'allim as the primary source supported by relevant contemporary scholarly literature. The findings show that Az-Zarnuji outlines three fundamental criteria for an educator: al-a'lam (professionally competent and knowledgeable), al-awra’ (morally upright and avoiding sinful acts), and al-asann (mature and experienced). According to Az-Zarnuji, a teacher is not merely an instructor but also a moral and spiritual guide (murshid) who directs learners to orient their educational goals toward attaining the pleasure of Allah SWT. This ethically and spiritually infused pedagogical model is highly relevant to contemporary efforts to strengthen teacher professionalism, ideally integrating academic competence, moral integrity, and spiritual depth. The thought of Az-Zarnuji therefore provides a valuable conceptual foundation for developing a model of teacher professionalism that is rooted in Islamic educational values while remaining responsive to the demands of modern education.